Fase analítica en el diagnóstico de infecciones del tracto urinario en el laboratorio de microbiología del hospital general IESS Ibarra - Andrade Cadena, Cesar David Licenciado (2024)
Urinary tract infections (UTIs) are globally considered the third most common cause of infections after respiratory tract infections. Therefore, it is crucial to use diagnostic tools such as the Urinalysis (UA) and urine culture, ensuring a correlation between them to achieve an accurate and timely diagnosis for appropriate antimicrobial therapy, thereby optimizing time and human resources in the laboratory and hospital. To evaluate the compliance with the analytical phase in the diagnosis of UTIs in the Microbiology Laboratory of the IESS General Hospital in Ibarra. A cross-sectional, descriptive, observational, and prospective study with a mixed approach was conducted, applying a checklist to assess compliance with the analytical phase. The process and subsequent analysis of the chemical examination using the URIT-1600 equipment and the microscopic examination using the URIT-1280 equipment were carried out. For the urine culture processing, calibrated loop inoculation (0.01 mL) was performed, followed by identification and sensitivity testing using the PHOENIX M50 system.A total of 204 urine samples were analyzed, for which the checklist of internal procedures established by the institution for both UA and urine culture analysis of each sample was reviewed. The results indicated no statistically significant relationship between the measured variables and the urine culture outcome. Regarding the isolation of pathogens identified in the study, Escherichia coli was found to be the primary causative agent of UTI, accounting for 57% of cases. Mixed flora (polymicrobial contamination) was identified in 12% of samples, interpreted as sample contamination. Klebsiella pneumoniae and Enterobacter cloacae, both significant hospital-associated bacteria, were found in fourth and fifth places with a prevalence of 7%, and other Enterobacterial pathogens accounted for 17%. A Pearson correlation test was conducted to determine the correlation between UA and urine culture, demonstrating a strong relationship between bacteria presence and urine culture results. In contrast, a binomial logistic regression test revealed an 86.3% accuracy rate in predicting both negative and positive urine culture results. There was a moderate correlation between the presence of pyocytes and urine culture, with a predictive value of 77.5%, indicating a good predictor of negative results but less precise for positive urine culture results. It was observed that the predictive value for pyocytes could be improved when associated with bacterial presence. Meanwhile, a null correlation was found between xiii squamous cells and urine culture results, indicating contamination during sample collection. Based on these results, exclusion criteria for urine culture inoculation can be considered, suggesting modifications and implementation of internal urine culture procedures. The evaluation of the analytical phase determined that there is no relationship between variables that did not meet the UA and urine culture analysis procedure, indicating that they do not influence the final examination outcome for either UA or urine culture. Different pathogenic agents were identified, with E. coli being the most prevalent. The correlation between UA and urine culture was established, demonstrating that bacteriuria and pyuria in UA aid in predicting bacterial growth in urine culture. Modifications to the urine culture procedure and the sample reception and rejection procedures were proposed.